Splintered politics of memory and community resistance. Issue 5 (9th June 2020) - Cornell, Josephine; Seedat, Mohamed; Malherbe, Nick; Suffla, Shahnaaz
Abstract: Oral history presents an especially effective way of exploring the multitudinous, contradictory, and contextual meanings that are attached to the notion of community. In this study, we argue for narrative‐discourse analysis as a critical means of studying contested community memories. We rely on focus group discussions and individual interviews to explore oral histories of state‐sanctioned relocation of residents of Thembelihle, a low‐income community in Johannesburg, South Africa. Our analysis revealed the sharply splintered politics that characterizes oral histories of this community. We argue that oral histories, in their contradictory and visceral fullness, are able to point toward a politics of resistance that is sensitive to inequalities, and that are willed toward emancipatory future‐building. We conclude by underlining the need for community psychologists to engage with a politics of memory that is sensitive to power differentials, historiography, and broader currents of oppression.